Experimentally derived axial stress–strain relations for two-dimensional materials such as monolayer graphene. (January 2015) - Androulidakis, Ch.; Tsoukleri, G.; Koutroumanis, N.; Gkikas, G.; Pappas, P.; Parthenios, J.; Papagelis, K.; Galiotis, C.
Abstract: A methodology is presented here for deriving true experimental axial stress–strain curves in both tension and compression for monolayer graphene through the shift of the 2D Raman peak (Δ ω ) that is present in all graphitic materials. The principle behind this approach is the observation that the shift of the 2D wavenumber as a function of strain for different types of PAN-based fibres is a linear function of their Young's moduli and, hence, the corresponding value of Δ ω over axial stress is, in fact, a constant. By moving across the length scales we show that this value is also valid at the nanoscale as it corresponds to the in-plane breathing mode of graphene that is present in both PAN-based fibres and monolayer graphene. Hence, the Δ ω values can be easily converted to values of σ in the linear elastic region without the aid of modelling or the need to resort to cumbersome experimental procedures for obtaining the axial force transmitted to the material and the cross-sectional area of the two-dimensional membrane.